Does digitalisation democratise opera? : audience engagement and diversity at the Bavarian State Opera - Babić, Filip (Taideyliopiston Sibelius-Akatemia, 2026)
This thesis examines the impact of digitalisation on audience engagement at the Bavarian State Opera, a major publicly funded opera house that has actively developed digital initiatives since 2021. Drawing on four expert interviews with internal and external actors involved in the institution's digital development, complemented by document analysis and digital platform review, the study investigates how digital tools shape access, diversity, and audience engagement in a classical music institution. The research follows a qualitative, interpretive single-case study design, with data analysed through thematic coding across three analytical categories: institutional context, digital initiatives, and audience engagement. The findings show that digitalisation has expanded informational and opportunity access, reaching geographically distant and mobility-restricted audiences, and lowering barriers for younger visitors through subsidised digital platforms. However, the socio-economic and cultural composition of the physically attending audience has not changed significantly. The study identifies several structural conditions that constrain what digital transformation can achieve, including governance lag, capacity and infrastructure deficits, and the economic model of publicly funded opera. These conditions shape the processes of technology adoption, measurement, and strategy implementation, and ultimately determine the outcomes of the digital investment. The study further examines the technoideological positioning of the institution in relation to AI adoption, the structural loyalty crisis facing the whole sector, and the implications of digital leadership literacy for sustained institutional transformation. The BSO is analysed as a best-case scenario, and its findings are considered in relation to the broader performing arts sector. The thesis concludes that digitalisation is a necessary but insufficient condition for audience democratisation in opera. Structural change at the level of funding models, governance frameworks, and cultural policy, is required to address what digital strategy alone cannot deliver.
Keywords: audience engagement; cultural access; artificial intelligence in the arts; Bavarian State Opera; digitalisation; audience; performing arts; artificial intelligence; fi=taidehallinto|sv=Arts Management|en=Arts Management|